An After‐School Snack of Raisins Lowers Cumulative Food Intake in Young Children. Issue 1 (21st June 2013) - Patel, Barkha P.; Bellissimo, Nick; Luhovyy, Bohdan; Bennett, Lorianne J.; Hurton, Evelyn; Painter, James E.; Anderson, G. Harvey
Abstract Snacks are an important part of children's dietary intake, but the role of dried fruit on energy intake in children is unknown. Therefore, the effect of ad libitum consumption of an after‐school snack of raisins, grapes, potato chips, and chocolate chip cookies on appetite and energy intake in twenty‐six 8‐ to 11‐y‐old normal‐weight (15th to 85th percentile) children was examined. On 4 separate weekdays, 1 wk apart, children (11 M, 15 F) were given a standardized breakfast, morning snack (apple), and a standardized lunch. After school, children randomly received 1 of 4 ad libitum snacks and were instructed to eat until "comfortably full." Appetite was measured before and 15, 30, and 45 min after snack consumption. Children consumed the least calories from raisins and grapes and the most from cookies (P < 0.001). However, weight of raisins consumed was similar to potato chips (about 75 g) and lower compared to grapes and cookies (P < 0.009). Raisins and grapes led to lower cumulative food intake (breakfast + morning snack + lunch + after‐school snack) (P < 0.001), while the cookies increased cumulative food intake (P < 0.001) compared to the other snacks. Grapes lowered appetite compared to all other snacks (P < 0.001) when expressed as a change in appetite per kilocalorie of the snack. Ad libitum consumption of raisins has potential as an after‐school snack to achieve low snack intake prior to dinner, similar to grapes, compared to potato chips, and cookies in children 8 to 11 y old.